2007
DOI: 10.3892/ijmm.20.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Novel effect of estrogen on RANK and c-fms expression in RAW 264.7 cells

Abstract: Temporomandibular disorder (TMD), a progressive disease entity, and osteoarthrosis preferentially affect females, denoting a possible role of estrogen. Using RAW 264.7 cells, the expression of estrogen receptors (ERs) α and ß and the consequent effect of estrogen was investigated. We present the novel detection of ER ß expression in RAW 264.7 cells. Furthermore, we innovatively demonstrated the increase in expression of both ER α and ß, as well as RANK and c-fms, with estrogen treatment. However, a decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
(31 reference statements)
1
9
0
2
Order By: Relevance
“…Abubaker et al (29) found ER α immunoreactivity in the articular disc of human TMJs; however, Campbell et al (5) found no such immunoreactivity in the articular disc of a TMJ obtained from a TMD patient. In our previous study (30), with the use of Western blotting and PCR amplification, we were able to demonstrate the novel detection of ER ß and confirmed presence of ER α in RAW 264.7 cells (representing macrophage-like type A synovial linning cells). In this study we showed expression of ER α and ß in HFLS (synovial linning cells type B), thus exploring both kinds of synovial lining cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abubaker et al (29) found ER α immunoreactivity in the articular disc of human TMJs; however, Campbell et al (5) found no such immunoreactivity in the articular disc of a TMJ obtained from a TMD patient. In our previous study (30), with the use of Western blotting and PCR amplification, we were able to demonstrate the novel detection of ER ß and confirmed presence of ER α in RAW 264.7 cells (representing macrophage-like type A synovial linning cells). In this study we showed expression of ER α and ß in HFLS (synovial linning cells type B), thus exploring both kinds of synovial lining cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study (30) we showed that estrogen increased expression of c-fms in macrophage-like cells. In the present study, we detected the expression of M-CSF/CSF-1 and c-fms in ATDC5 and HFLS cells and we further demonstrated increased expression of M-CSF/CSF-1 and c-fms via estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported the effects of estrogen on RaW 264.7 and hFls cells, regarding inflammation and bone resorption [15,16]. In the current study we investigated the expression of PMca isoforms in RaW 264.7 and hFls cells, as well as, the modulatory effect of 17β-estradiol on the expression levels of PMca isoforms.…”
Section: Western Blottingmentioning
confidence: 99%
“…another reported the effect of 17β-estradiol on sarcoplasmic reticulum Ca 2+ -atPase in h9c2 cells [14]; neither report assessed the direct effects of 17β-estradiol on PMCA, nor the relevantly affected PMca isoform. We investigated the effects of our previously reported optimal concentration of 10 -8 M 17β-estradiol [15,16] on hFls and RaW 264.7 cells. the specific ca 2+ -atPase activity in RaW 264.7 and hFls treated for 24 hours decreased to 62% and 94% respectively, compared to that of their control (100%) (Fig.…”
Section: Cell Homogenatementioning
confidence: 99%
“…The effects of estrogen on osteoblasts include both direct effects resulting in increased bone formation, and an indirect effect, via an osteoblast-mediated interaction with preosteoclasts and osteoclasts, resulting in decreased bone resorption (Galal et al 2007). Estrogen exerts its indirect effect through products secreted by osteoblasts that include receptor activator of nuclear factor kB ligand (RANKL), colony-stimulating factor-1 (CSF1), and osteoprotegerin (OPG), which are important in differentiation and maturation of osteoclasts.…”
Section: Introductionmentioning
confidence: 99%